Population and Distribution of Some Soil MesoFauna in the Inactive Tailing Deposition Areas of Freeport Indonesia, Timika-Papua - Djuuna, Irnanda Aiko Fifi (UNIVERSITY OF LAMPUNG, 2013)
Soil fauna has played an important role in ecosystem functioning, especially as ecosystem engineers which contribute to soil fertility in tropical environment. A tailing deposition area is one habitat that has several types of soil fauna to live and growth as well as involves in the decomposition of organic matter. The objective of this study was to examine the number and distribution of soil fauna in the tailing area of Freeport Indonesia Mining and Gold Company, Timika. The study was located in some inactive tailing deposition areas in between Double Levee of the lowland area of ModADA (Modification Ajkwa Deposition Areas). Samples were taken from inactive tailing as 198 of ModADA for soil and soil fauna, the Kuadran Method was used to collecting soil fauna on the soil surface and in the soil. There were 17 types/ordo of soil fauna in the study area and the highest number was a group of ants (Hymenoptera/Formicidae). Population density (PD) and relative density (RD) of soil fauna (Formicidae) ranged from 0.03-2.41 Individu m-2 (PD) and 0.07-6.50% (RD). Both PD and RD were likely to increase as the number of soil fauna increase. The distribution of most soil fauna were found as a clump, while Pulmonata (Gastropods) were distributed normally in the tailing areas. The number and types (ordo) of these soil fauna had showed that inactive tailing deposition areas were considered a good habitat for soil fauna.Key words: Distribution, population, soil fauna, tailing[How to Cite: Djuuna IAF. 2013. Population and Distribution of Some Soil MesoFauna in the Inactive Tailing Deposition Areas of Freeport Indonesia, Timika-Papua. J Trop Soils 18 (3): 225-229. Doi: 10.5400/jts.2013.18.3.225][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.3.225]REFERENCESAdianto.1993.Agricultural Biology of Animal Manure, Organic Fertilizer and Insecticides. Bandung: Penerbit Alumni (in Indonesian).Anderson JM and JS Ingram. 1993. Tropical soil biology and fertility: A Handbook of Methods, 2nd ed. CAB International. Wallingford. UK, 221 pp.Battigelli JP. 2011. Exploring the World Beneath your Feet – Soil Mesofauna as Potential Biological Indicators of Success in Reclaimed Soils. Proceedings - Tailings and Mine Waste Vancouver, BC.Behan-Pelletier VM. 1999.Oribatid mite biodiversity in agroecosystems: role as bioindicators. Agric Ecosyst Environ 74: 411-423. Brussard L. 1998. Soil fauna, guilds, functional groupsand ecosystem processes. Appl Soil Ecol 9: 123-136.De Ruiter PC, B Griffiths and JC Moore. 2002. Biodiversity and Stability in Soil Ecosystems: Patterns, Processes and the Effects of Disturbance. In: M Loreau, S Naeem and P Inchausti (eds.). Biodiversity and Ecosystem Functioning: a current synthesis. Oxford University Press, Oxford, UK, pp. 102-113.Djuuna IAF, H Siby and S Baan.2008. Population and Distribution of Soil Fauna on the Below ground of Forest Trees in Gunung Meja Forest Areas of Manokwari. J Beccariana 1: 6. Fitter AH, CA Gilligan, K Holling Worth, A Kleczkowski, RM Twyman, JW Pitchford and the Members of the Nerc Soil Biodiverrsity Programme. 2005. Biodiversity and ecosystem function in soil. Funct Ecol 19: 369-377.Hanafiah KA, I Anas, A Napoleon and N Gofar. 2005. Biologi Tanah : Ekologi dan Makrobiologi Tanah. Edisi 1, PT Raja Grafindo Persada. Jakarta,165 pp. (in Indonesian). Picaud F and DP Petit. 2007.Primary succession of Orthoptera on mine tailings: role of vegetation. Ann de la Soc Entomol de France 43: 69-79Rusek J. 1998. Biodiversity of Collembola and their functional role in the ecosystem. Biodiver Conserv 7: 1207-1219.Sackett TE, AT Classen, and NJ Sanders. 2010.Linking soil food web structure to above and below ground ecosystem processes: ameta-analysis. Oikos 119: 1984-1992.Shao Y, W Zhang, J Shen, L Zhou, H Xia, W Shu, H Ferris and S Fu. 2008. Nematodes as indicators of soil recovery in tailings of a lead/zinc mine. Soil Biol Biochem 40: 2040-2046.Suin NM. 2003. The Ecology of Soil Fauna. Penerbit Bumi Aksara Jakarta (in Indonesian).Sugiyarto. 2000.The Biodiversity of soil macro fauna on the different age of sengon in RPH Jatirejo, Kabupaten Kediri. Biodiversitas 1: 47-53. (in Indonesian).Sugiyarto, M Pujo and Nursihmiati. 2001. Relationship between the Soil Meso Fauna Biodiversity and Belowground Vegetation in Some Forest Trees of Jobolarangan. Biodiversitas 2: 140-145 (in Indonesian)Wallwork JA. 1970. Ecology of Soil Animals. London: Mc.Graw-Hill. 283 pp.Wallwork JA.1976. The Distribution and Diversity of Soil Fauna. Academic Press Inc. (London). 355 pp.